TINJAUAN HUKUM TERHADAP PENGGUNAAN GPS PADA KENDARAAN SEWA DALAM PERSPEKTIF PERLINDUNGAN PRIVASI KONSUMEN - Santosa, Malik Buana; Octarina, Nynda Fatmawati (Fakultas Hukum Universitas Narotama, 2025)
ABSTRACT The development of Global Positioning System (GPS) and voice recorder technology in rental car vehicles offers real benefits in improving fleet security, tracking in the event of loss, and monitoring renter behavior. However, the installation of these devices without explicit notification and consent has the potential to violate the right to privacy—a human right protected by Article 12 of the Universal Declaration of Human Rights (UDHR), Article 28G paragraph (1) of the 1945 Constitution, and clarified in Law Number 27 of 2022 concerning Personal Data Protection. This study uses a juridical-normative method with a statutory regulatory approach and the concept of the right to privacy to analyze the legality of installing GPS and voice recorders in rental cars. The results of the study indicate that (1) GPS installation is permissible as long as it is accompanied by transparency, written consent, and data access is limited to vehicle security purposes only; (2) voice recorders have the potential to violate criminal provisions on wiretapping because they record private conversations without permission; and (3) national regulations do not yet provide detailed technical guidelines regarding the consent mechanism, storage time limits, and audits of data use. This study recommends updating rental agreement clauses, implementing the principle of privacy by design in devices, and strengthening state oversight to ensure the protection of renters' privacy rights as well as legal certainty for car rental businesses. Keywords: privacy, GPS, car rental